Effect of Organizational Citizenship Behaviour, Quality of Work Life and Motivation on Employee Performance - Said, Muh; Mustaking, Mustaking (Jurnal Office, 2023)
This study aims to analyse: 1) The effect of Organizational Citzenship Behaviour, on the performance of employees of the Transmigration Service of West Sulawesi Province. 2) The effect of quality of work life, on the performance of employees of the Transmigration Service of West Sulawesi Province. 3) The influence of Motivation on employees of the Transmigration Service of West Sulawesi Province. This research uses quantitative methods. The research was conducted at the Transmigration Office of West Sulawesi Province. This study distributed questionnaires to 60 respondents. The method used is quantitative method by testing the hypothesis, namely Validity Test, Reliability Test, Classical Assumption Test, Multiple Regression Analysis, T Test, F Test, and Coefficient of Determination. The results showed that Organizational Citzenship Behaviour had a positive and significant effect on the performance of employees of the Transmigration Service of West Sulawesi Province, on the second variable Quality of work life had a positive and significant effect on the performance variables of employees of the Transmigration Service of West Sulawesi Province, on the third variable motivation had a positive and significant effect on the performance of the Transmigration Service of West Sulawesi Province. In the simultaneous test, the variables of Organizational Citzenship Behaviour, Quality of work life, and motivation, have a positive and significant effect on employee performance, Transmigration Service of West Sulawesi Province. while the Determination test has a contribution to employee performance of 61.3%, while the rest is influenced by other variables not included in the study.